Synthesis of peptidomimetic compounds as HIV-1 protease inhibitors - Kayembe, Jean-Pierre (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
This research project has involved the design, synthesis and evaluation of novel peptidomimetics compounds as HIV-1 protease inhibitors. Here is presented one-step, two-step and three-step syntheses and the in vitro bio-assay studies of a series of fully characterized peptidomimetics as HIV-1 protease inhibitors candidate using the shortest and most cost effective synthetic routes. The first series of compounds were accessed via a synthetic elaboration of Morita-Baylis-Hillman adducts by a Michael addition with benzylamine, proline or glycine esters to afford a series of Î²-amino-Î²'-hydroxycarboxylate esters in moderate to good yields. Base-catalyzed cyclization of non-benzylated aza-Michael adducts afforded a series of coumarin-3-hydroxy-2-methylenepropanoate esters in moderate yields. The uncatalyzed direct amidation of diethyl tartrate/tartaric acid and tartaric acid osazone with selected amines/amino acids afforded a series of C2-symmetrical and unsymmetrical 1,2-dihydroxycarboxylates in moderate to very high yields. All the synthesized compounds were fully characterized using spectroscopic techniques. These conjugates, designed as potential HIV-1 inhibitors, were tested against the HIV-1 protease enzyme. A number of these ligands have exhibited inhibition levels and IC50 values comparable to ritonavir, permitting, therefore, their identification as lead compounds for the development of novel inhibitors.
Keywords: Protease inhibitors; HIV (Viruses); HIV infections Treatment; Peptidomimetics